A Systematic Review of Football Tactics Learning in Physical Education Curriculum - Ridwan, Andi; Adil, Ahmad (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This systematic review examines the effectiveness of football tactics learning within physical education (PE) curricula over the past decade. A comprehensive analysis of 30 peer-reviewed studies from national and Scopus-indexed journals reveals that game-centered instructional models, especially the Teaching Games for Understanding (TGfU) and Tactical Games Model (TGM), significantly enhance students’ tactical awareness, decision-making skills, and overall engagement. Across multiple studies, TGfU-based interventions resulted in an average 25% improvement in tactical knowledge and a 30% increase in student motivation compared to traditional teaching methods (García-Ceberino et al., 2020; Barba-Martín et al., 2020). Additionally, tactical learning embedded in real-game scenarios improved technical skills by 18% (Olthof et al., 2020), demonstrating the integrative benefits of these models. The review identifies key factors influencing the successful implementation of these approaches, including teacher training and contextual adaptation to diverse learner backgrounds. Despite positive outcomes, several gaps persist, such as limited longitudinal studies assessing long-term retention of tactical knowledge and the need for standardized assessment tools. This study recommends further research to explore hybrid pedagogical models combining tactical and skill-based instruction, alongside enhanced professional development for educators. The findings underscore the importance of innovative, student-centred teaching methods to promote cognitive, affective, and physical domains in football education. Ultimately, integrating tactical learning in PE supports holistic student development and fosters lifelong engagement in physical activity and sports.